Hydrogen Storage in Carbon and Oxygen Co‐Doped Porous Boron Nitrides. (16th October 2020) - Weng, Qunhong; Zeng, Lula; Chen, Zhiwei; Han, Yuxin; Jiang, Kang; Bando, Yoshio; Golberg, Dmitri
Abstract: Fuel cell vehicles powered by hydrogen are particularly attractive and competitive among rapidly developing new energy‐driven automobiles. One critical problem for this type of vehicles is the high cost for hydrogen storage due to the lack of efficient and low‐pressure hydrogen storage technologies. In the frame of development of hydrogen physisorption‐relied materials, attention has mostly been paid to the textural designs of porous materials, including specific surface area, pore volume, and pore size. However, based on the hydrogen physisorption mechanism, hydrogen adsorption energy on a material surface is another key factor with regard to hydrogen uptake capacity. Herein, solid experimental evidences are provided and it is also proven that the chemical states of porous boron nitride (BN) materials remarkably affect their hydrogen adsorption performances. The developed carbon and oxygen co‐doped BN microsponges exhibit the hydrogen uptake capacity per specific surface area of 2.5–4.7 times larger than those of undoped BN structures. These results show the importance of chemical state modulations on the future designs of high‐performance hydrogen adsorbents based on physisorption approaches. Abstract : Carbon and oxygen co‐doped porous boron nitride structures are demonstrated to remarkably enhance the affinities of H2 molecules. The hydrogen uptake capacity per specific surface area for this type of materials is 2.5–4.7 times higher than that with undoped BN structures, suggesting the importance of material bonding/chemical state modulations on designing advanced hydrogen storage materials.